Korelasi Umur Dengan Kesehatan Mental Sebagai Gambaran Pemenuhan Tugas Perkembangan Remaja Usia Sekolah - Madu Pamangin, Lisda Oktavia; Adimuntja, Natalia Paskawati; Pamangin, Wilda Wijayani (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2025)
Mental health problems in adolescents have an impact on risky behavior. Preventive measures can be taken through early detection in adolescents. This study aims to analyze the correlation of age with emotional problems, behavioral problems, hyperactivity problems, and peer problems in school-age adolescents in Jayapura City. The study design used was cross-sectional. The population taken was adolescents aged 11-17 years who were studying in junior high school-high school. The sample size was 397 respondents and was selected using multistage random sampling technique in 12 secondary schools spread across 4 districts (sub-districts) in Jayapura City. Data processing and analysis were assisted by SPSS 21 software and Spearman Correlation test (CI 95%, α = 0.05). The results showed that there was a positive correlation between age and emotional problem scores (p= 0.038, r= 0.104) with a weak correlation level and small relationship strength. A negative correlation was also found between age and behavioral problem scores (p= 0.010, r= -0.129). the level of correlation between age and behavioral problem scores is a weak correlation with a small strength of relationship. Therefore, it can be concluded that the age of adolescents has a significant correlation with the emotional and behavioral conditions of adolescents.